ANALISIS PENGARUH STRATEGI PEMBELAJARAN BERBASIS MASALAH TERHADAP PENDIDIKAN VOKASIONAL - Ananda Surya Lesmana (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This article is created to analyze the influence of problem-based learning on vocational education through literature review methods from various sources discussing problem-based learning strategies on vocational education. Problem- based learning refers to a learning model that allows students to overcome problems through the stages of scientific methods and receive problem-bound science while widening real-life problem-solving skills. Vocational education is a type of education that aims to prepare individuals with the practical skills necessary to enter the workforce. This approach is geared towards exploring the influence of problem- based learning strategies in expanding students’ skills and knowledge in vocational fields. A review of literature investigates a wide range of studies that have been conducted in this title, including the practical and theoretical implications of implementing such strategies. The results of the analysis present an in-depth understanding of the contribution of problem-based learning strategies that can be used to curriculum development and learning in vocational schools